2016
DOI: 10.1002/elan.201600674
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Hydrazine Sensor Based on Co(OH)2 Nanoflakes Electrochemically Deposited on MWCNTs

Abstract: We delineate the electrochemical preparation of cobalt hydroxide nanoflakes Co(OH)2 NFs on multi‐walled carbon nanotubes (MWCNTs) by potentiostatic methods. The preparation was done on the surface of glassy carbon electrode (GCE). The prepared nanocomposite was characterized by field emission scanning electron microscopy (FESEM), X‐ray diffraction spectroscopy (XRD) and X‐ray photo electron spectroscopy (XPS). The resulting f‐MWCNTs/Co(OH)2 NFs modified GCE exhibits a good electrocatalytic activity for the oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…As shown in Figure c, the Co 2p spectrum shows two characteristic peaks with binding energies of 781.6 and 797.5 eV, corresponding to Co 2p 3/2 and Co 2p 1/2 . The positions and distance between these two peaks (Δ = 15.9 eV) indicate that Co exists in the Co­(OH) 2 form, consistent with reports in the literature. , We also collected an XPS spectrum from a pure Co­(OH) 2 reference sample (the blue spectrum in Figure c), and found that it shows exactly the same peak positions and peak distance as do the Co-Ex-MoS 2 sample. The XPS results show that the majority of Co species are in Co­(OH) 2 form.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As shown in Figure c, the Co 2p spectrum shows two characteristic peaks with binding energies of 781.6 and 797.5 eV, corresponding to Co 2p 3/2 and Co 2p 1/2 . The positions and distance between these two peaks (Δ = 15.9 eV) indicate that Co exists in the Co­(OH) 2 form, consistent with reports in the literature. , We also collected an XPS spectrum from a pure Co­(OH) 2 reference sample (the blue spectrum in Figure c), and found that it shows exactly the same peak positions and peak distance as do the Co-Ex-MoS 2 sample. The XPS results show that the majority of Co species are in Co­(OH) 2 form.…”
Section: Resultssupporting
confidence: 87%
“…In addition, the O 1s spectrum of Co-Ex-MoS 2 shows three deconvoluted peaks centered at 532.7, 531.6, and 530.5 eV (Figure d). The main peak, located at 531.6 eV, is assigned to oxygen ions (O lattice ) in Co­(OH) 2 , , and peaks at 532.7 and 530.5 eV are assigned to absorbed water and oxide species. , The selective area electron diffraction (SAED) pattern of the Co-Ex-MoS 2 also confirms the Co species are Co­(OH) 2 (Figure S6). All the above results confirm that the intercalated Co species are Co­(OH) 2 .…”
Section: Resultsmentioning
confidence: 85%
“…[1][2][3][4][5] However, N 2 H 4 is highly toxic, corrosive and also identified as carcinogenic agent which has adverse effect on health. 6 Therefore, it is of great significance to develop sensitive methods for the detection of N 2 H 4 . Nowadays numerous methods such as spectrophotometry, fluorimetry, chromatography, electrochemistry have been reported for the quantification of N 2 H 4 .…”
mentioning
confidence: 99%